Research in personnel and human resources management. Vol. 28 - Martocchio, Joseph J.; Liao, Hui, 1975- (Research in personnel and human resources management,, 2009)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 28 of "Research in Personnel and Human Resources Management" ("RPHRM") contains seven papers on important issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field. This collection of papers represents excellent scholarship and illustrates the truly interdisciplinary character of the field.